Alphacoronavirus Detection in Lungs, Liver, and Intestines of Bats from Brazil - Bittar, Cíntia [UNESP]; Machado, Rafael Rahal Guaragna [UNESP]; Comelis, Manuela Tosi [UNESP]; Bueno, Larissa Mayumi [UNESP]; Beguelini, Mateus Rodrigues [UNESP]; Morielle-Versute, Eliana [UNESP]; Nogueira, Maurício Lacerda; Rahal, Paula [UNESP] (Springer Nature, 2019)
Bats are flying mammals distributed worldwide known to host several types of Coronavirus (CoV). Since they were reported as the probable source of spillover of highly pathogenic CoV into the human population, investigating the circulation of this virus in bats around the world became of great importance. We analyzed samples from 103 bats from two distinct regions in Brazil. Coronavirus from the Alphacoronavirus genus was detected in 12 animals, 11 from São José do Rio Preto—SP region and 1 from Barreiras—BA region, resulting in a prevalence of 17.18% and 2.56% respectively. The virus was detected not only in intestines but also in lungs and liver. Phylogenetic analysis based on nsP12 genomic region suggests that the sequences group according to host family and sampling location. Studies on the circulation of these viruses in bats remain important to understand the ecology and evolutionary relationship of these pathogens.
Keywords: Alphacoronavirus; Bats; Coronavirus; Phylogeny